Балкова модель при розрахунку міцності залізобетонних плит при продавлюванні - Клімов, Юлій (КНУБА, 2021)
Представлена балкова модель для розрахунку міцності залізобетонних плит при продавлюванні. В рамках цієї моделі гранична поперечна сила, яку сприймає плита при продавлюванні, визначається як сума граничних поперечних сил, що сприймають дві перпендикулярні балки змінної ширини. The beams model of computation of punching shear forces in reinforced concrete slabs on the basis the general approach to strength computation of shear appearing under punching shear is developed. Within the framework of the developed method the ultimate shear received by a slab under punching shear is determined as the sum of the ultimate shear received by two perpendicular beams of a variable wideness.
Beams Design Model for Punching Shear Capacity of Reinforced Concrete Slabs
Keywords: модель балкова; розрахунок міцності залізобетонних плит; beams design model; reinforced concrete slabs